Diversity of gold trapping in colloform, low crystalline AS, FE - rich mesostasis - Castromil area, Dúrico-Beirão mining district, northern Portugal - Gomes, C. Leal (2016)
Castromil gold area is part of Durico-Beirdo mining district, located not far from Porto (Northern Portugal). Several generations of gold were distinguished in the district, two of them related with stages of remobilization of primary gold. A new generation of gold is described in this study. A set of penetrative shear surfaces, main shear ruptures and veins are concentrated in the vicinity of a tectonic contact between a cataclastic, weathered, porphyritic granite and regional metassedimentary to metavolcanic Silurian formations. In some structural domains of the granite, where pervasive argillic alteration showed a major heterogeneity, secondary and ore-minerals and para-crystalline materials were characterized by optical microscopy, XRD and SEM-EDS. The systematic of the mineralization stages reveal the following sequence: a pyrite and minor chalcopyrite in metapelite enclaves; b - phyllitic alteration of granite, related to a low sulphidation stage - main gold stage in veins early hydrothermal; c - phyllitic to argillic complex alteration of cataclastic pophyritic granite and augen leucogranite, related to crack-seal of earlier veins and late infill of chalcedony and comb-quartz remobilization of early sulphides and disseminated sulphide impregnation of host-rocks late hydrothermal; d - dissolution of previous feldspar and sulphide crystals followed by the coating, infill and replenishment of dissolution cavities and vugs oxidative evolution late hydrothermal to early supergenic; e - sequence of late oxidative stages producing assemblages, referred as AMORPHOUS FERRIC ARSENATES (AFA), AMORPHOUS IRON SULPHOARSENATES (AFSA) and HYDROUS FERRIC OXIDES (HFO) - late hydrothermal to early supergenic. There is a strong spatial correlation between the increment of Au mineralization and the geometric progress of dissolution and pseudomorphosis of earlier minerals (especially sulphides) and signs of BYO dispersion. The arsenopyrite alteration products in the area of Castromil are crystalline Fe (III) arsenates (scorodit